2012
DOI: 10.4103/2278-0513.106274
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of maxilla mimicking neurofibroma

Abstract: Osteosarcoma (OS) is a primary malignant bone tumor producing osteoid or bone. It occurs less frequently in the jaws and in maxilla occurrence is rare. Jaws are less affected compared to long bones (4-13%). The mean age of occurrence is third to fourth decade. The histopathologic features of OS are highly variable. Herein, we report a rare case of a 72 year old female patient with a swelling in right posterior maxilla, whose clinical, radiographic findings were non-specific, An initial incisional biopsy confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…But the present case appears to have developed de novo as no history of pre-existing disease was associated which makes this report unusual. 9,22,23 History of extraction of second molar ,one year back, could be considered as predisposing factor as extraction wound didnot heal and the swelling appeared at the same site.Similar findings were reported by Prabhu. S .et al 21, as well as Daffer 24 in their studyin which many patients had a history of extraction before the onset of the lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the present case appears to have developed de novo as no history of pre-existing disease was associated which makes this report unusual. 9,22,23 History of extraction of second molar ,one year back, could be considered as predisposing factor as extraction wound didnot heal and the swelling appeared at the same site.Similar findings were reported by Prabhu. S .et al 21, as well as Daffer 24 in their studyin which many patients had a history of extraction before the onset of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…33 Misdiagnosed cases of osteosarcoma frequently reported in various literatures.Rosilene et al, reported a case of osteosarcoma of mandible initially resembling of periapical lesion and after initial endodontic treatment, a significant increase in the size of the lesion occurred 34 PriyankaDebta 35et al also misdiagnosed a case of osteosarcoma as benign cystic lesion which recurred aggressively to cause extensive destruction. CD Mounesh at el misdiagnosed asneurofibroma 23 . It could be hypothesized that the first lesion presented by the patient was a low-grade central osteosarcoma, since this neoplasia is often misdiagnosed radiographically, clinically and microscopically as fibrous dysplasia.…”
Section: Discussionmentioning
confidence: 99%